Tuberculosis Exacerbates HIV-1 Infection through IL-10/STAT3-Dependent Tunneling Nanotube Formation in Macrophages - Shanti Souriant (Cell Reports, 2019)
Summary: The tuberculosis (TB) bacillus, Mycobacterium tuberculosis (Mtb), and HIV-1 act synergistically; however, the mechanisms by which Mtb exacerbates HIV-1 pathogenesis are not well known. Using in vitro and ex vivo cell culture systems, we show that human M(IL-10) anti-inflammatory macrophages, present in TB-associated microenvironment, produce high levels of HIV-1. In vivo, M(IL-10) macrophages are expanded in lungs of co-infected non-human primates, which correlates with disease severity. Furthermore, HIV-1/Mtb co-infected patients display an accumulation of M(IL-10) macrophage markers (soluble CD163 and MerTK). These M(IL-10) macrophages form direct cell-to-cell bridges, which we identified as tunneling nanotubes (TNTs) involved in viral transfer. TNT formation requires the IL-10/STAT3 signaling pathway, and targeted inhibition of TNTs substantially reduces the enhancement of HIV-1 cell-to-cell transfer and overproduction in M(IL-10) macrophages. Our study reveals that TNTs facilitate viral transfer and amplification, thereby promoting TNT formation as a mechanism to be explored in TB/AIDS potential therapeutics. : Tuberculosis is a clear, yet confounding, risk factor for HIV-1-induced morbidity and mortality. In this issue, Souriant et al. reveal that a tuberculosis-associated microenvironment triggers IL-10/STAT3-dependent tunneling nanotube formation in M(IL-10) macrophages, which promotes HIV-1 exacerbation during co-infection. M(IL-10) macrophage accumulation is also observed in vivo in co-infected subjects. Keywords: AIDS, HIV-1, tuberculosis, Mycobacterium tuberculosis, co-infection, macrophage, monocyte, IL-10, STAT3, viral spread, tunneling nanotubes, biomarker